1979
DOI: 10.1093/ajcn/32.3.630
|View full text |Cite
|
Sign up to set email alerts
|

A review of body composition studies with emphasis on total body water and fat

Abstract: Tritiated water meausres a volume 4 to 15% body weight larger than that by desiccation, and, at present, only 0.5 to 2.0% of the overestimation can be explained by the exchange of hydrogen of tritiated water with those of the proteins and carbohydrates of the body. The remainder of the error is unexplained. Water in the lumen of the gut is an appreciable percentage of total body water (TBW) in many mammalian species, with the pig and the human as possible exceptions, and it should be considered an integral par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
145
0
7

Year Published

1987
1987
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(166 citation statements)
references
References 81 publications
14
145
0
7
Order By: Relevance
“…25 FM was obtained as the difference between body weight and FFM. Whole-body glucose uptake (M value, in mmol per min per kg of FFM) was determined by averaging the exogenous glucose infusion rates during the last 40 min of the clamp after correction for changes in glucose levels in a distribution volume of 250 ml kg À1 .…”
Section: Discussionmentioning
confidence: 99%
“…25 FM was obtained as the difference between body weight and FFM. Whole-body glucose uptake (M value, in mmol per min per kg of FFM) was determined by averaging the exogenous glucose infusion rates during the last 40 min of the clamp after correction for changes in glucose levels in a distribution volume of 250 ml kg À1 .…”
Section: Discussionmentioning
confidence: 99%
“…This study therefore compared TBW predicted by foot-to-foot BIA with those measured using a deuterium oxide dilution technique. Deuterium oxide dilution is accepted as one of the 'gold standard' techniques for measuring TBW (Sheng & Huggins, 1979), although the measured dilution space needs to be corrected for overestimation of TBW because of the exchange of isotope with nonaqueous hydrogen (Schoeller et al, 1980). In our laboratory, in vitro tests have shown that the accuracy of deuterium dilution for measuring a water volume is approximately 1%.…”
Section: Discussionmentioning
confidence: 99%
“…We have compared the predicted total body water from a new foot-to-foot impedance machine to that measured via a deuterium oxide dilution technique. The latter technique is accepted as one of thè gold standard' methods for measuring total body water (Sheng & Huggins, 1979), although it is important to correct the measured dilution space for the overestimation of total body water due to exchange of isotope with nonaqueous hydrogen (Schoeller et al, 1980). In our laboratory, in vitro tests have shown that the accuracy of deuterium dilution for measuring a water volume is approximately 1%.…”
Section: Discussionmentioning
confidence: 99%